Vgl1, a multi-KH domain protein, is a novel component of the fission yeast stress granules required for cell survival under thermal stress. - Wen, W; Stevenson, A; Wang, C; Chen, H; Kearsey, S; Norbury, C; Watt, S; Bähler, J; Wang, S (2010)
Multiple KH-domain proteins, collectively known as vigilins, are evolutionarily highly conserved proteins that are present in eukaryotic organisms from yeast to metazoa. Proposed roles for vigilins include chromosome segregation, messenger RNA (mRNA) metabolism, translation and tRNA transport. As a step toward understanding its biological function, we have identified the fission yeast vigilin, designated Vgl1, and have investigated its role in cellular response to environmental stress. Unlike its counterpart in Saccharomyces cerevisiae, we found no indication that Vgl1 is required for the maintenance of cell ploidy in Schizosaccharomyces pombe. Instead, Vgl1 is required for cell survival under thermal stress, and vgl1Δ mutants lose their viability more rapidly than wild-type cells when incubated at high temperature. As for Scp160 in S. cerevisiae, Vgl1 bound polysomes accumulated at endoplasmic reticulum (ER) but in a microtubule-independent manner. Under thermal stress, Vgl1 is rapidly relocalized from the ER to cytoplasmic foci that are distinct from P-bodies but contain stress granule markers such as poly(A)-binding protein and components of the translation initiation factor eIF3. Together, these observations demonstrated in S. pombe the presence of RNA granules with similar composition as mammalian stress granules and identified Vgl1 as a novel component that required for cell survival under thermal stress.